Students' Scientific Literacy in Critical Thinking Skills in Science Learning: A Bibliometric Analysis from the Scopus Database - Lubis, Jalilah Azizah; Pantiwati, Yuni; Rahardjanto, Abdulkadir (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to analyze the trends, patterns, and dynamics of research on students' scientific literacy in relation to critical thinking skills in science learning through a bibliometric approach. The research seeks to identify dominant topics, international collaboration networks, and contributions from institutions and countries, as well as to explore the integration of scientific literacy with critical thinking skills in educational contexts. Data were collected from the Scopus database using keywords